The option value of municipal liquidity: Evidence from federal lending cutoffs during COVID-19 - Andrew Haughwout; Benjamin L. Hijmans; Or Shachar (Federal Reserve Bank of New York, 2021)
We estimate the option value of municipal liquidity by studying bond market activity and public sector hiring decisions when government budgets are severely distressed. Using a regression discontinuity (RD) design, we exploit lending eligibility population cutoffs introduced by the federal sector's Municipal Liquidity Facility (MLF) to study the effects of an emergency liquidity option on yields, primary debt issuance, and public sector employment. We find that while the announcement of the liquidity option improved overall municipal bond market functioning, lower-rated issuers additionally benefited from direct access to the facility - their bonds traded at higher prices and were issued more frequently, suggesting a potential credit-risk sharing channel on top of the Fed's role as liquidity-provider of last resort. Local governments, by contrast, responded to emergency liquidity measures by recalling a greater share of service-providing government employees (mostly educational institution workers), but recalls were only sustained for higher-rated municipalities. This hiring responsiveness is consistent with the hypothesis that large government furloughs might have over-weighted the worst possible outcomes based on past experience. Together, the results suggest that municipalities would likely have been more distressed absent the emergency liquidity.
Keywords: G14; G18; H74; 330; municipal debt; state and local governments; COVID-19; Federal Reserve lending facilities